INTEGRASI PENDIDIKAN KARAKTER DALAM KURIKULUM MADRASAH IBTIDAIYAH: ANALISIS TEORITIS DAN PRAKTIS (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to analyze the integration of character education in the Madrasah Ibtidaiyah curriculum from theoretical and practical perspectives. The research method uses a qualitative approach with library research through relevant literature analysis. The results show that the integration of character education is based on the Islamic concept of tarbiyah which includes the pillars of aqidah, syariah, and akhlaq with a holistic approach through subjects, school culture, and habituation. The main character values include religious, noble morals, and social values that are instilled through exemplary strategies, habituation, and active learning. The role of teachers as role models, comprehensive evaluation systems, and school-family-community synergy are key success factors. The main challenges in the form of limited teacher competence and environmental inconsistencies can be overcome through continuous training and strengthening cooperation. The study concludes that Madrasah Ibtidaiyah has a strategic position in shaping a Muslim generation that is intelligent and has noble character through systematic and comprehensive integration of character education.